Analysis Of Company Bankruptcy Potential During The Covid-19 Pandemic: A Study Of The Transportation And Health Sector In Indonesia In 2020-2021 - Muhammad Bilal Selostannu Rizki; Imo Gandakusuma (Jurnal Indonesia Sosial Teknologi, 2023)
The Covid-19 pandemic that occurred has damaged the economy of Indonesia and even the world. This poses a threat to companies in various sectors. Thus, this study aims to examine the role of financial ratios (current ratio, debt to asset ratio, return on assets, total asset turnover, sales growth) and macroeconomic factors (lending rate) in predicting potential bankruptcy conditions in transportation and health companies in Indonesia during the Covid-19 pandemic. The study was conducted with the Altman Z-Score of developing countries measured by the panel data regression method. The data used in this study were secondary data obtained from the Thomson-Reuter data stream. The population of this study is companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2021 period with a sample of 69 companies. Based on the results of the research, it was found that the factors of the current ratio, debt-to-asset ratio, and sales growth have a significant effect on the potential bankruptcy of the company. This research is limited by relevant data and time during the Covid-19 pandemic.